Clinical Manifestations and Experience of Diagnosis and Treatment of Lymphoid Tissue Infection Caused by Pseudomonas Aeruginosa - LI Yafeng (Zhongguo quanke yixue, 2023)
Pseudomonas aeruginosa is a conditional pathogen, which is a common pathogen in nosocomial infections and relatively rare in community infections. At present, there are few reports on the clinical manifestations of Pseudomonas aeruginosa infection, especially regarding the lymphoid tissue infection caused by Pseudomonas aeruginosa. This paper reported a case of lymphoid tissue infection caused by Pseudomonas aeruginosa, summarized its clinical manifestations and treatment process, in order to improve the clinical understanding of the diagnosis and treatment of this disease.